Single-doped coated lithium manganese iron phosphate positive electrode material and preparation method thereof, and lithium battery

By introducing rare earth metal-doped carbon dots and nitrogen atom doping into the lithium manganese iron phosphate positive electrode material, the problem of low conductivity of the material is solved, and the cycling and electrochemical performance of lithium batteries is significantly improved.

CN119181792BActive Publication Date: 2025-02-11HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD

Patent Information

Application Number
CN202411686511.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-11
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The conductivity of lithium manganese iron phosphate materials is low, resulting in a reduced circulation performance of lithium batteries.

Method used

A single-doped coated lithium manganese iron phosphate positive electrode material is adopted, and its raw materials include lithium source, phosphorus source, iron source, manganese source, carbon source and rare earth metal doped organic metal frame. Through ball milling, spray drying and calcining, etc. Preparation, rare earth metal doped carbon doping and nitrogen atom doping are introduced to improve conductivity.

Benefits of technology

The conductivity and cyclic performance of the positive electrode material are improved, the electrochemical performance of lithium batteries is enhanced, and the balance of energy density and cyclic performance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181792B_ABST
    Figure CN119181792B_ABST
Patent Text Reader

Abstract

This invention discloses a single-doped coated lithium manganese iron phosphate cathode material, its preparation method, and a lithium battery, belonging to the field of lithium battery technology. The raw materials of the cathode material include a lithium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a rare earth metal-doped organometallic framework. The mass content of the rare earth metal-doped organometallic framework is 2%-5%, and the mass content of the carbon source is 1%-4%. In the preparation process of the single-doped coated lithium manganese iron phosphate cathode material, the present invention uses nitrogen atoms as carbon and nitrogen sources. Introducing nitrogen atom doping into the carbon coating of the cathode material can reduce the polarization of the material and enhance the reversibility of the battery. The rare earth metal-doped organometallic framework and carbon source in the present invention can serve as the total carbon source. Increasing the total carbon source content in the cathode material can improve the polarization of the electrode material. However, the total carbon content should not be too high, as excessive carbon will lead to an increase in internal resistance, which in turn will lead to a decrease in its cycle performance and affect the electrochemical performance of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a single-doped coated lithium manganese iron phosphate positive electrode material and a preparation method thereof, and a lithium battery. Background Art

[0002] Lithium iron manganese phosphate (LiMn x Fe 1-x PO4) is a new type of phosphate lithium-ion battery cathode material formed by doping a certain proportion of manganese (Mn) on the basis of lithium iron phosphate (LiFePO4). Through the doping of manganese, on the one hand, the advantages of iron and manganese can be effectively combined, and on the other hand, manganese and iron are both located in the fourth period subgroup and adjacent in the periodic table, with similar ionic radius and some chemical properties, so doping will not significantly affect the original structure (olivine-type stable structure).

[0003] Compared with lithium iron phosphate, the high voltage characteristic of manganese makes lithium manganese iron phosphate have a higher voltage platform, which also leads to a higher energy density when the specific capacity is the same. Under the same conditions, the energy density is 10%-20% higher than that of lithium iron phosphate, but the disadvantage is that the introduction of manganese reduces the conductivity of the material. In the existing process of preparing lithium manganese iron phosphate, manganese is easily unevenly distributed, and lithium manganese phosphate material is formed locally, which makes the conductivity of the obtained lithium manganese iron phosphate material low, reduces the discharge capacity, and thus reduces the cycle performance of the lithium battery. Summary of the invention

[0004] The object of the present invention is to provide a single-doped coated lithium manganese iron phosphate positive electrode material and a preparation method thereof, and a lithium battery, so as to solve the problem of low conductivity of the lithium manganese iron phosphate material and reduced cycle performance of the lithium battery.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A single-doped coated lithium manganese iron phosphate positive electrode material, wherein the raw materials of the positive electrode material include a lithium source, a phosphorus source, an iron source, a manganese source, a carbon source and a rare earth metal-doped organic metal framework, wherein the mass content of the rare earth metal-doped organic metal framework is 2%-5%; the mass content of the carbon source is 1%-4%.

[0007] Furthermore, the rare earth metal-doped organic metal framework is prepared by ultrasonic method using dimethylimidazole, zinc acetate and rare earth metal-doped carbon dots; the dosage ratio of the rare earth metal-doped carbon dots, dimethylimidazole and zinc acetate is 0.7g:0.068mol:0.7mol.

[0008] Furthermore, the rare earth metal doped carbon dots are prepared by a microwave method: sucrose solution is used as a carbon source, diethylene glycol is used as a solvent, concentrated sulfuric acid is used as a carbonization promoter, and rare earth metal chloride is used as a doping substance.

[0009] Furthermore, the mass fraction of the sucrose solution is 30%; the mass fraction of the concentrated sulfuric acid is 98%; the concentration of the rare earth metal chloride solution is 2 g / L; and the dosage ratio of the sucrose solution, concentrated sulfuric acid, rare earth metal chloride solution and diethylene glycol is 40 mL: 1.5 mL: 3 mL: 30 mL.

[0010] Furthermore, the rare earth metal chloride is at least one of yttrium chloride, lanthanum chloride, cerium chloride and samarium chloride.

[0011] Furthermore, the molar ratio of the total amount of the iron source and the manganese source, the lithium source, and the phosphorus source is 1:1-1.05:1.

[0012] Further, the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium nitrate and lithium acetate;

[0013] The iron source is at least one of ferrous sulfate, ferrous nitrate, ferrous acetate and ferrous oxalate;

[0014] The manganese source is at least one of manganese sulfate, manganese nitrate and manganese acetate;

[0015] The carbon source is at least one of glucose, sucrose, polyethylene glycol and citric acid;

[0016] The phosphorus source is at least one of diammonium phosphate, ammonium phosphate and phosphoric acid.

[0017] A method for preparing a single-doped coated lithium manganese iron phosphate positive electrode material, characterized in that it comprises the following steps:

[0018] The first step is to mix a lithium source, a phosphorus source, an iron source, a manganese source, a carbon source, a rare earth metal-doped organic metal framework and a solvent, and perform ball milling under a nitrogen atmosphere;

[0019] The second step is to spray-dry the slurry obtained after ball milling to obtain a powder;

[0020] The third step is to calcine the powder in an inert atmosphere or a nitrogen atmosphere to obtain a single-doped coated lithium manganese iron phosphate positive electrode material.

[0021] Furthermore, the solvent is one of water and ethanol; and the calcination temperature is 700-750°C.

[0022] A lithium battery comprises the above-mentioned single-doped coated lithium manganese iron phosphate positive electrode material.

[0023] Beneficial effects of the present invention:

[0024] The present invention provides a single-doped coated lithium manganese iron phosphate positive electrode material. By adding a rare earth metal-doped organic metal framework, the rare earth metal-doped organic metal framework in the present invention can be used as a doped carbon source. The doped carbon coating material is introduced into the lithium manganese iron phosphate by in-situ carbon generation, and is embedded in the positive electrode material after sintering, thereby improving the conductivity of the positive electrode material and further improving the cycle performance of the lithium battery.

[0025] In the single-doped coated lithium manganese iron phosphate positive electrode material prepared by the present invention, a rare earth metal-doped organic metal framework is used as a carbon source and a nitrogen source, and nitrogen atom doping (derived from the rare earth metal-doped organic metal framework) is introduced into the carbon coating of the positive electrode material, which can reduce the polarization degree of the material and enhance the reversibility of the battery; the rare earth metal-doped organic metal framework also introduces rare earth ions into the positive electrode material, which can appropriately reduce the content of trivalent manganese and inhibit the dissolution of manganese, and an appropriate amount of rare earth ions are doped into the olivine structure of the lithium manganese iron phosphate, thereby increasing the conductivity of the positive electrode material and thus improving the cycle performance, and a synergistic effect is produced between the rare earth metal and the carbon dots in the rare earth metal-doped organic metal framework, thereby effectively enhancing the electrochemical performance of the lithium battery.

[0026] The rare earth metal-doped organic metal framework and carbon source (organic carbon source) in the present invention serve as the total carbon source, increasing the total carbon source content in the positive electrode material, and can improve the polarization degree of the electrode material. However, the total carbon content should not be too large, as too much carbon will increase the internal resistance, thereby causing a decrease in its cycle performance and affecting the electrochemical properties of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described below in conjunction with the accompanying drawings.

[0028] Figure 1 is a scanning electron microscope image of the positive electrode material prepared in Example 1 of the present invention;

[0029] Figure 2 It is a scanning electron microscope image of the positive electrode material prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In order to make the lithium iron manganese phosphate positive electrode material have good conductivity and cycle performance, the present invention provides a single-doped coated lithium iron manganese phosphate positive electrode material and a preparation method and a lithium battery, by adding rare earth metal doped organic metal framework, through the rare earth metal doped organic metal framework in the synergistic effect between the rare earth metal and carbon dots, thereby effectively enhancing the electrochemical performance of the lithium battery.

[0032] In a first aspect, the present invention provides a single-doped coated lithium manganese iron phosphate positive electrode material, wherein the raw materials of the positive electrode material include a lithium source, a phosphorus source, an iron source, a manganese source, a carbon source and a rare earth metal-doped organic metal framework, wherein the mass content of the rare earth metal-doped organic metal framework is 2%-5% (referring to the rare earth metal-doped organic metal framework accounting for 2%-5% of the total mass of the lithium source, phosphorus source, iron source, manganese source, carbon source and rare earth metal-doped organic metal framework); in some specific embodiments, the mass content of the rare earth metal-doped organic metal framework can be 2%, 3%, 4%, 5% or the like, or a range between any two contents.

[0033] The mass content of the carbon source is 1%-4% (referring to the carbon source accounting for 1%-4% of the total mass of the lithium source, phosphorus source, iron source, manganese source, carbon source, and rare earth metal-doped organic metal framework). In some specific embodiments, the mass content of the carbon source can be 1%, 2%, 3%, 4%, etc., or a range between any two contents.

[0034] Furthermore, the rare earth metal doped organic metal framework is prepared by ultrasonic method using dimethylimidazole, zinc acetate and rare earth metal doped carbon dots; the dosage ratio of the rare earth metal doped carbon dots, dimethylimidazole and zinc acetate is 0.7g:0.068mol:0.7mol. Dimethylimidazole and zinc acetate are used as raw materials for preparing the organic metal framework. The introduction of nitrogen atoms in the organic metal framework can form vacancies, providing active sites for the embedding of lithium ions, thereby improving the electrochemical properties of the positive electrode material. In addition, the introduction of rare earth metals can improve the carbon quantum dots sp 2 The proportion of hybridized carbon atoms further improves the conductive properties.

[0035] Furthermore, the rare earth metal doped carbon dots are prepared by a microwave method: sucrose solution is used as a carbon source, diethylene glycol is used as a solvent, concentrated sulfuric acid is used as a carbonization promoter, and rare earth metal chloride is used as a doping substance.

[0036] Furthermore, the mass fraction of the sucrose solution is 30%; the mass fraction of the concentrated sulfuric acid is 98%; the concentration of the rare earth metal chloride solution is 2 g / L; and the dosage ratio of the sucrose solution, concentrated sulfuric acid, rare earth metal chloride solution and diethylene glycol is 40 mL: 1.5 mL: 3 mL: 30 mL.

[0037] Furthermore, the rare earth metal chloride is one of yttrium chloride, lanthanum chloride, cerium chloride and samarium chloride.

[0038] Furthermore, the molar ratio of the total amount of the iron source and the manganese source, the lithium source, and the phosphorus source is 1: 1-1.05: 1. In some specific embodiments, the molar ratio of the iron source to the manganese source is 1: 1, which is used to compare the relationship between the mass content and the total amount of different carbon sources and rare earth metal-doped organic metal frameworks.

[0039] Further, the lithium source is at least one of lithium carbonate, lithium hydroxide, lithium nitrate and lithium acetate;

[0040] The iron source is at least one of ferrous sulfate, ferrous nitrate, ferrous acetate and ferrous oxalate;

[0041] The manganese source is at least one of manganese sulfate, manganese nitrate and manganese acetate;

[0042] The carbon source is at least one of glucose, sucrose, polyethylene glycol and citric acid;

[0043] The phosphorus source is at least one of diammonium phosphate, ammonium phosphate and phosphoric acid.

[0044] In a second aspect, the present invention provides a method for preparing a single-doped coated lithium manganese iron phosphate positive electrode material, characterized in that it comprises the following steps:

[0045] The first step is to mix a lithium source, a phosphorus source, an iron source, a manganese source, a carbon source, a rare earth metal-doped organic metal framework and a solvent, and perform ball milling under a nitrogen atmosphere;

[0046] The second step is to spray-dry the slurry obtained after ball milling to obtain a powder;

[0047] The third step is to calcine the powder in an inert atmosphere or a nitrogen atmosphere to obtain a single-doped coated lithium manganese iron phosphate positive electrode material.

[0048] Furthermore, the solvent is one of water and ethanol, and the calcination temperature is 700-750° C. If the sintering temperature is too high, the product particle size will be larger, which is not conducive to the improvement of performance. If the temperature is too low, the product reaction will be incomplete and the product performance will be poor.

[0049] In a third aspect, the present invention provides a lithium battery comprising the above-mentioned single-doped coated lithium manganese iron phosphate positive electrode material.

[0050] Preparation Example 1

[0051] The rare earth metal doped organic metal framework is prepared by the following steps:

[0052] According to the proportion, 40 mL of 30% sucrose solution, 1.5 mL of concentrated sulfuric acid and 3 mL of 2 g / L yttrium chloride solution were added to 30 mL of diethylene glycol. After ultrasonic dispersion, the mixture was heated at 750 W for 1 min in a microwave. After filtering with a microporous membrane with a pore size of 0.22 μm, the solution was concentrated by rotary evaporation to obtain rare earth metal-doped carbon dots.

[0053] According to the proportion, 0.7 g of rare earth metal-doped carbon dots and 10 mL of deionized water were mixed, and after ultrasonic dispersion, 0.068 mol of dimethylimidazole was added and stirred, and then ultrasonic dispersion was performed to obtain a dispersion. The obtained dispersion was added into 25 mL of 0.27 mol / L zinc acetate aqueous solution, and the ultrasound was continued for 30 min. After standing, centrifugation, ethanol washing, and vacuum drying at 60°C, a rare earth metal-doped organic metal framework was obtained.

[0054] Preparation Example 2: This preparation example differs from Preparation Example 1 in that the rare earth metal chloride is different:

[0055] The rare earth metal doped organic metal framework is prepared by the following steps:

[0056] According to the proportion, 40 mL of 30% sucrose solution, 1.5 mL of concentrated sulfuric acid and 3 mL of 2 g / L lanthanum chloride solution were added to 30 mL of diethylene glycol. After ultrasonic dispersion, the mixture was heated at 750 W for 1 min in a microwave. After filtering with a microporous membrane with a pore size of 0.22 μm, the solution was concentrated by rotary evaporation to obtain rare earth metal-doped carbon dots.

[0057] According to the proportion, 0.7 g of rare earth metal-doped carbon dots and 10 mL of deionized water were mixed, and after ultrasonic dispersion, 0.068 mol of dimethylimidazole was added and stirred, and then ultrasonic dispersion was performed to obtain a dispersion. The obtained dispersion was added into 25 mL of 0.27 mol / L zinc acetate aqueous solution, and the ultrasound was continued for 30 min. After standing, centrifugation, ethanol washing, and vacuum drying at 60°C, a rare earth metal-doped organic metal framework was obtained.

[0058] Preparation Example 3: Compared with Preparation Example 1, this preparation example does not introduce rare earth metal-doped carbon dots:

[0059] The specific steps for preparing the organic metal framework precursor are as follows:

[0060] According to the proportion, 0.068 mol of dimethylimidazole and 10 mL of deionized water were mixed, ultrasonically dispersed, stirred and mixed, and ultrasonically dispersed to obtain a dispersion. The obtained dispersion was added to 25 mL of 0.27 mol / L zinc acetate aqueous solution, and ultrasonication was continued for 30 minutes. After standing, centrifugation, ethanol washing, and vacuum drying at 60°C, an organic metal framework precursor was obtained.

[0061] Preparation Example 4: This preparation example is similar to Preparation Example 1, but does not introduce carbon dots to prepare a rare earth metal-doped organic metal framework:

[0062] Compared with Preparation Example 1, the specific steps of the organic metal framework precursor in this preparation example are as follows:

[0063] To 10 mL of 2 g / L yttrium chloride solution, 0.068 mol of dimethylimidazole was added, the mixture was stirred and mixed, and then ultrasonic dispersion was performed to obtain a dispersion. The obtained dispersion was added to 25 mL of 0.27 mol / L zinc acetate aqueous solution, and ultrasonic dispersion was continued for 30 min. The dispersion was allowed to stand, centrifuged, washed with ethanol, and then vacuum dried at 60° C. to obtain a rare earth metal-doped organic metal framework.

[0064] Example 1

[0065] This embodiment provides a method for preparing a single-doped coated lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0066] The first step is to mix lithium carbonate, ammonium dihydrogen phosphate, ferrous oxalate, manganese sulfate, glucose, the rare earth metal doped organic metal framework prepared in Preparation Example 1 and anhydrous ethanol, and ball mill them under a nitrogen atmosphere; wherein the mass content of the rare earth metal doped organic metal framework is 2% (referring to the rare earth metal doped organic metal framework accounting for 2% of the total mass of lithium carbonate, ammonium dihydrogen phosphate, ferrous oxalate, manganese sulfate, glucose and rare earth metal doped organic metal framework); the mass content of glucose is 4% (glucose accounts for 4% of the total mass of lithium carbonate, ammonium dihydrogen phosphate, ferrous oxalate, manganese sulfate, glucose and rare earth metal doped organic metal framework). The molar ratio of the total amount of ferrous oxalate and manganese sulfate, lithium carbonate and ammonium dihydrogen phosphate is 1:1-1.05:1. The molar ratio of ferrous oxalate and manganese sulfate is 1:1.

[0067] The second step is to spray-dry the slurry obtained after ball milling to obtain powder; the spray-drying temperature is 200°C;

[0068] In the third step, the powder was calcined at 700°C under a nitrogen atmosphere to obtain a single-doped coated lithium manganese iron phosphate positive electrode material. See the scanning electron microscope image for details. Figure 1 As shown, the particles are complete and round, and the doping and coating effects are good.

[0069] Example 2

[0070] Compared with Example 1, the mass content of the rare earth metal-doped organic metal framework in this example is 3%; the mass content of glucose is 3%, and the other raw materials and preparation process remain the same as those in Example 1.

[0071] Example 3

[0072] Compared with Example 1, the mass content of the rare earth metal-doped organic metal framework in this example is 4%; the mass content of glucose is 2%, and the other raw materials and preparation process remain the same as those in Example 1.

[0073] Example 4

[0074] Compared with Example 1, the mass content of the rare earth metal-doped organic metal framework in this example is 5%; the mass content of glucose is 1%, and the other raw materials and preparation process remain the same as those in Example 1.

[0075] Example 5

[0076] Compared with Example 1, the rare earth metal-doped organic metal framework in this example is replaced by the organic metal framework precursor prepared in Preparation Example 2, and the other raw materials and preparation process remain unchanged.

[0077] Comparative Example 1

[0078] The difference between this comparative example and Example 1 is that the rare earth metal-doped organic metal framework in Example 1 is replaced by the organic metal framework precursor prepared in Preparation Example 3, and the other raw materials and preparation process remain unchanged.

[0079] Comparative Example 2

[0080] The difference between this comparative example and Example 1 is that the rare earth metal-doped organic metal framework in Example 1 is replaced by the organic metal framework precursor prepared in Preparation Example 4, and the other raw materials and preparation process remain unchanged.

[0081] Comparative Example 3

[0082] The difference between this comparative example and Example 1 is that the rare earth metal-doped organic metal framework in Example 1 is replaced with glucose (the total amount of glucose is 6%), and the other raw materials and preparation process remain unchanged.

[0083] Comparative Example 4

[0084] The difference between this comparative example and Example 1 is that the mass content of glucose is adjusted to 6% (i.e., the total amount of the organic metal framework precursor and glucose is 8%), and the other raw materials and preparation process remain unchanged. The scanning electron microscope image of the prepared sample is shown in FIG. Figure 2 As shown, the particles are incomplete and contain particles of different sizes and morphologies.

[0085] The performance tests were conducted on Examples 1 to 5 and Comparative Examples 1 to 4. The electrochemical performance test was conducted using a button cell. The test assembly method was as follows: the positive electrode material samples, binders (polyvinylidene fluoride, PVDF) and conductive agents (acetylene carbon black) prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were accurately weighed in a mass ratio of 8:1:1 using an electronic analytical balance and placed in a mortar and ground for about 30 minutes. The samples were then transferred to a container, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added dropwise. The mixture was mixed evenly on a magnetic stirrer until the slurry had no obvious granularity (about 5 to 8 hours). The slurry was evenly coated on an aluminum foil using a coater and placed in a vacuum drying oven at 110°C for drying for 12 hours. The pole pieces were then rolled using a roller machine and cut into discs with a diameter of 12 mm using a cutter. The discs were weighed using an analytical balance to obtain the loading amount of the active material. Finally, a CR2032 button cell was assembled in a glove box with an argon atmosphere using a metal lithium sheet as the counter electrode and a Celgard 2500 composite membrane as the diaphragm. The electrolyte used was 1 mol / L lithium hexafluorophosphate. The assembly order was: positive electrode shell-positive electrode sheet-electrolyte-diaphragm electrolyte-metal lithium sheet gasket-spring sheet-negative electrode shell.

[0086] The electrochemical performance test of button batteries was carried out using a blue electric test cabinet. The test temperature was 25±5℃ and the test voltage range was set to 2V~4.5V. The test results are shown in Table 1:

[0087]

[0088] From the test results, it can be seen that the lithium battery test sample prepared with the single-doped coated lithium manganese iron phosphate positive electrode material prepared by the present invention has good cycle performance, and the capacity retention rate can still reach 98.56% after 500 cycles at 1C.

[0089] The rare earth metal doped organic metal framework in the present invention can be used as a doping carbon source, and as a carbon source and a nitrogen source in the preparation process of a single doped coated lithium manganese iron phosphate positive electrode material. According to the comparison of the results of Example 1 and Comparative Examples 1 to 4, it can be seen that the introduction of nitrogen atom doping (derived from the rare earth metal doped organic metal framework) in the carbon coating of the positive electrode material can reduce the polarization degree of the material, thereby enhancing the reversibility of the battery; in addition, the rare earth metal doped organic metal framework also introduces rare earth metal doped carbon dots in the positive electrode material, which can appropriately reduce the content of trivalent manganese and inhibit the dissolution of manganese, and in the olivine structure of the lithium manganese iron phosphate An appropriate amount of rare earth metal-doped carbon dots is added to increase the conductivity of the positive electrode material, thereby improving the cycle performance. Therefore, a synergistic effect is produced between the rare earth metal and the carbon dots in the rare earth metal-doped organic metal framework, thereby effectively enhancing the electrochemical performance of the lithium battery. From the comparison between Example 1 and Comparative Example 3, it can be seen that the effect of only introducing rare earth elements on improving battery performance is limited. After doping, the energy density of the positive electrode will decrease to a certain extent, which is not conducive to the improvement of the battery energy density. In the present invention, rare earth metal-doped carbon dots are used to introduce carbon dots and rare earth elements to achieve a balance between energy density and cycle performance, thereby better improving battery performance.

[0090] According to the comparison of the results of Example 1 and Comparative Example 4, it can be seen that too much carbon will lead to an increase in internal resistance, which in turn leads to a decrease in its cycle performance and affects the electrochemical performance of the lithium battery. The rare earth metal-doped organic metal framework and carbon source (organic carbon source) in the present invention are used as the total carbon source, which increases the mass content of the total carbon source in the positive electrode material. Combined with the introduction of the rare earth metal-doped organic metal framework in this application (the introduction of carbon quantum dots (referred to as carbon dots) can promote the formation of a carbon layer structure by roasting, but the amount of glucose used in Comparative Example 4 is too much, resulting in incomplete or overly large particles, and the prepared sample contains particles of different particle sizes and morphologies), the compaction density of the material is affected, which is not conducive to the improvement of performance.

[0091] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Single doped coated lithium manganese iron phosphate positive electrode material, characterized in that: The raw materials of the positive electrode material include a lithium source, a phosphorus source, an iron source, a manganese source, a carbon source and a rare earth metal-doped organic metal framework, wherein the mass content of the rare earth metal-doped organic metal framework is 2%-5%; the mass content of the carbon source is 1%-4%; The rare earth metal doped organic metal framework is prepared by ultrasonic method using dimethylimidazole, zinc acetate and rare earth metal doped carbon dots; the dosage ratio of the rare earth metal doped carbon dots, dimethylimidazole and zinc acetate is 0.7g:0.068mol:0.7mol; The rare earth metal doped carbon dots are prepared by a microwave method: sucrose solution is used as a carbon source, diethylene glycol is used as a solvent, concentrated sulfuric acid is used as a carbonization promoter, and rare earth metal chloride is used as a doping substance.

2. The single-doped coated lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The mass fraction of the sucrose solution is 30%; the mass fraction of the concentrated sulfuric acid is 98%; the concentration of the rare earth metal chloride solution is 2 g / L; the dosage ratio of the sucrose solution, concentrated sulfuric acid, rare earth metal chloride solution and diethylene glycol is 40 mL: 1.5 mL: 3 mL: 30 mL.

3. The single-doped coated lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The rare earth metal chloride is at least one of yttrium chloride, lanthanum chloride, cerium chloride and samarium chloride.

4. The single-doped coated lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of the total amount of the iron source and the manganese source, the lithium source and the phosphorus source is 1:1-1.05:

1.

5. The single-doped coated lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The lithium source is at least one of lithium carbonate, lithium hydroxide, lithium nitrate and lithium acetate; The iron source is at least one of ferrous sulfate, ferrous nitrate, ferrous acetate and ferrous oxalate; The manganese source is at least one of manganese sulfate, manganese nitrate and manganese acetate; The carbon source is at least one of glucose, sucrose, polyethylene glycol and citric acid; The phosphorus source is at least one of diammonium phosphate, ammonium phosphate and phosphoric acid.

6. The method for preparing a single-doped coated lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The steps include: The first step is to mix a lithium source, a phosphorus source, an iron source, a manganese source, a carbon source, a rare earth metal-doped organic metal framework and a solvent, and perform ball milling under a nitrogen atmosphere; The second step is to spray-dry the slurry obtained after ball milling to obtain a powder; The third step is to calcine the powder in an inert atmosphere or a nitrogen atmosphere to obtain a single-doped coated lithium manganese iron phosphate positive electrode material.

7. The method for preparing the single-doped coated lithium manganese iron phosphate positive electrode material according to claim 6, characterized in that: The solvent is one of water and ethanol; and the calcination temperature is 700-750°C.

8. A lithium battery, characterized in that It comprises the single-doped coated lithium manganese iron phosphate positive electrode material as described in any one of claims 1-5.

Citation Information

Patent Citations

  • Modified lithium iron phosphate material, preparation method and application thereof

    CN108199041A

  • Preparation method and application of metal-doped carbon in-situ coated lithium iron phosphate electrode material

    CN114551823A

Cited By

  • Plasma activation assisted gradient in-situ carbonized lithium manganese iron phosphate positive electrode material and preparation method thereof

    CN122532124A